EVOLUTION OF THE FORMATION OF THE SYSTEM OF ENSURING ECONOMIC SECURITY - Диха, Валерій Валерійович; Таранюк, Олександр Вікторович (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2023)
The article substantiates that safety is the most important value of people’s social existence, a necessary basis for quality life and further development of mankind. At the present stage of civilisational development, safety issues have become of great relevance, since the mechanisms for ensuring safety in the global world are currently inactive. The resolutions, principles of coexistence, respect for rights and freedoms, etc. are violated, to put it mildly. The purpose of the article is to study the evolution of the system of ensuring economic security of the State. The article is based on general scientific and special methods of cognition. During the research, methods of analysis and synthesis, principles of formal logic, generalization, methods of inductive and deductive analysis were used. A systematic approach was used in the research process. The article examines the evolution of the system of ensuring economic security. It was found that security issues have been studied by thinkers since ancient times. Philosophers’ treatment of security issues has been systematized, and the main concepts of ensuring security have been singled out. The stages of the evolutionary formation of the state security system are described and the features of security at each stage are characterized. It is well-founded that a certain level of security is determined by economic and political conditions, as well as by the activities of relevant state bodies and organizations that contribute to the formation of the relevant state and perform regulatory functions. It is noted that the conceptual and categorical apparatus on issues of economic security, the identification and characteristics of the components of economic security gained active development only in the 20th century. The generalization and systematization of the work on the formation of the economic security system will contribute to the search for ways to ensure it in modern realities.